Development of E-Comic as a Physics Learning Media for Class X Students on Momentum and Impulse Materials - Giri Kartika; Azhar Azhar; Muhammad Nasir (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce an interesting and valid learning media so that it is suitable for use in physics learning in the form of an e-comic for class X students on Momentum and Impulse material. The research method used is R&D (Research and Development) with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The validity of the e-comic learning media was tested through aspects of material competence, aspects of material suitability, language aspects, display aspects, and usage aspects. The results of the validator's assessment of the material competence aspect are 4.33, the material suitability aspect is 4.33, the language aspect is 4.27, the display aspect is 4.43, and the usage aspect is 4.25. The validity of physics learning media in the form of e-comic in terms of all aspects is 4.32 with a very valid category. Thus, e-comic as a medium for learning physics for class X students on Momentum and Impulse material is declared valid and feasible be used as a medium for learning physics